Ṭaṭbiqu Ta’līmi Darsi al Hiwāri fī al Madrasati al ‘Āliyati al Islāmiyyati al Ḥukūmiyyati bi Bayākumbūh Sūmatrā al Gharbiyyati - Nurhasnah, Nurhasnah; Prihartini, Yogia (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2020)
The Arabic learning process is directed to encourage, guide, develop, and foster students' Arabic language skills, Arabic language skills will also support students in understanding the sources of Islamic teachings, such as the Al-Qur'an and Hadith, and other books that use Arabic . In the Arabic learning process, it is expected that students will have good abilities in learning Arabic. To achieve the expected objectives, the Hiwar learning strategy is to use the Hiwar (conversation) method. The lesson material consists of fluency in speaking by using Arabic.This research is a field research in the form of descriptive qualitative research. Data collection was carried out by interview, observation and documentation. The data analysis used is descriptive in the form of secondary data and primary data. In analyzing the data, it begins with examining the data, after the data is collected then its contents are clarified and analyzed, then interpreted and concluded. The Arabic learning process at MAN 1 Payakumbuh has been implemented in accordance with the existing curriculum, based on Content Standards (SI) and Graduates Competency Standards (SKL), which explains that learning Arabic at Islamic Senior High School is a process of activities directed at encouraging, guiding, develop and develop fushha Arabic language skills, by prioritizing the ability to read and understand reading material. The ability to speak and compose sentences is aimed at strengthening reading skills, which is the main goal of learning, namely the ability to communicate as well as a provision for understanding Islamic teachings from the original sources, namely Al-Quran and Al-hadith. The conclusion of this study is that it turns out that students are still not able to carry out good faith in Arabic and cannot use it in daily conversations, because the learning strategies used are still not optimal due to the lack of media and supporting infrastructure that support the learning process of Hiwar. So that it hasn't got maximum results.